Anti-fibrinolytics (lysine analogues) for the prevention of bleeding in patients with haematological disorders (Protocol) - Wardrop, D; Estcourt, L; Doree, C; Hopewell, S; Brunskill, S; Stanworth, S; Murphy, M (Cochrane Collaboration, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To determine the efficacy and safety of anti-fibrinolytics (lysine analogues) in preventing bleeding in patients with haematological disorders.